Segmentasi Pasar Penyedia Jasa Logistik (Third Party Logistics) di Indonesia - Sudrajat, Darjat (Binus Business Review, 2010)
Market segmentation is fundamental in marketing strategy and the first step of market-based strategy preparation, to strengthen its marketing efficiency, and creating opportunities for sales growth and profits. This also applies to market segmentation logistics service providers (TPL - Third Party Logistics), the market is highly developed in the last decade, so that the logistics service providers has to develop marketing strategies properly. The purpose of this research is to gain a better understanding of different industries that exist today and map the needs of the logistics services of TPL customers. Based on exploration research conducted, it can be found in conformities relating to the logistics industry from several companies, ie appropriateness to the complexity of logistics activities of some companies and degree of investment of TPL services company in conducting the activity. Logistics service provider market segmentation can be based on variable complexity of logistics activities, whether it is high, medium or low and variable degrees of investment in the company whether minor, major, or integrated/total. Companies in different industries can have the same logistic service requirements and companies in the same industry can have different logistic service requirements. Client companies for logistics service providers which product handling are classified as semi-complex is the most attractive customer segments for being penetrated. The industries are classified into this segment is automotive, food and beverage, animal food, ceramic, and plantation.Â